The European recognition of professional qualifications – a legal framework for the European citizenship - Torres, Raquel (2016)
This paper discusses the evolution of the requirements for recognition of professional qualifications within the European project. In order to do this, an explanation will, first, be given of the first legal measures and the subsequent period of transformation, which led to the legal framework that is in place today. Following this, a brief comment will be given on other political and legal movements that favored the implementation of the recognition systems in the European context, namely the Bologna and Copenhagen Processes that instigated a strong cooperation to achieve European common standards for the Member States’ educational systems. Finally, this legal evolution will inform this paper’s considerations of the implications this evolution will have on the construction of a European citizenship.